Pengaruh Penerapan Keselamatan Dan Kesehatan Kerja Terhadap Pencegahan Paparan Covid-19 Pada Tenaga Kesehatan Di RSUD DR.Djasamen Saragih Kota Pematang Siantar - Ripai Siregar; Armanda Prima (Program Studi Pendidikan Biologi, 2022)
The spread of the Covid-19 pandemic in the world is currently very aggressive, based on data from the WHO, there were 129 million cases of Covid-19 worldwide. In the critical period of the Covid-19 pandemic, health workers are professions who are at the forefront that play a direct role in preventing the spread of Covid-19, so the safety and security of health workers must always be considered. This study aims to determine how the application of K3 affects the prevention of exposure to Covid-19 in health workers. The research method used is descriptive quantitative with a cross sectional approach. This research was conducted at the dr. Djasamen Saragih, Pematangsiantar City from December 2020 to June 2021. The population of this study amounted to 230 with 70 research samples taken using simple random sampling technique. Data were analyzed using chi square test with = 0.05. The results of the bivariate analysis of all variables stated that there was an influence between the independent variables, namely: knowledge (P-value = 0.000), compliance with the use of PPE (P-value = 0.027), K3 regulations (P-value = 0.008), availability of PPE (P-value = 0.023) and the role of supervision ( Pvalue = 0.000) on the prevention of Covid-19 exposure to health workers. As an effort to prevent the spread of Covid-19, especially in the hospital environment, occupational safety and health must be implemented as optimally as possible, this can be done by making policies, conducting socialization and setting sanctions for workers who violate policies so that the number of health workers exposed to COVID-19 can be minimized